Dynamic Basis for dG•dT misincorporation via tautomerization and ionization - Kimsey, Isaac J. (Nature, 2018)
Tautomeric and anionic Watson-Crick-like mismatches play important roles in replication and translation errors through mechanisms that are not fully understood. Using NMR relaxation dispersion, we resolved a sequence-dependent kinetic network connecting G•T/U wobbles with three distinct Watson-Crick mismatches consisting of two rapidly exchanging tautomeric species (G(enol)•T/U⇌G•T(enol)/U(enol); population <0.4%) and one anionic species (G•T(−)/U(−); population ≈0.001% at neutral pH). Inserting the sequence-dependent tautomerization/ionization step into a minimal kinetic mechanism for correct incorporation during replication following initial nucleotide binding leads to accurate predictions of dG•dT misincorporation probability across different polymerases, pH conditions, and for a chemically modified nucleotide, and provides mechanisms for sequence-dependent misincorporation. Our results indicate that the energetic penalty for tautomerization/ionization accounts for ≈10(−2)−10(−3)–fold discrimination against misincorporation, which proceeds primarily via tautomeric dG(enol)•dT and dG•dT(enol) with contributions from anionic dG•dT(−) dominating at pH ≥8.4 or for some mutagenic nucleotides.